Tourist Engagement and Destination Loyalty Among Local Visitors in the Philippines - Eric S Parilla (Research Synergy Foundation, 2023)
This research aims to establish the relationship between the five components of engagement and the destination loyalty of 1,400 local visitors in the province of Ilocos Norte. Enthusiasm, attention, absorption, interaction, and identification were the variables of this study. The study included structural equation modeling and a questionnaire tailored to the pandemic-related alterations. The results of the inquiry demonstrated this zeal. Attention, interaction, and identification were the factors that influenced destination loyalty. Interaction has the greatest impact on a visitor's loyalty to a place; consequently, it is advised to improve this component. In addition, the report recommends that the provincial government and local tourism officials do more research to identify potential discrepancies between male and female visitor reactions.